Acute neurologic toxicity of palliative radiotherapy for brain metastases in patients receiving immune checkpoint blockade. Issue 4 (25th October 2018) - Arscott, W Tristram; Zhu, Simeng; Plastaras, John P; Maity, Amit; Alonso-Basanta, Michelle; Jones, Joshua
Abstract: Background: The interaction between immune checkpoint blockade (ICB) and radiation (RT) for brain metastases has not been well understood. Given that acute neurotoxicity from this combination is not well characterized, we reviewed patients receiving ICB and RT for brain metastases. Methods: Patients treated with ICB and cranial RT from 2010 through 2017 were reviewed. ICB and RT must have been administered within 30 days of each other. Treatment parameters, performance status, symptoms prior to treatment, and toxicity were extracted from the electronic medical record. Survival was calculated from the end of RT to last follow-up or death. Results: Seventy-eight patients were included. Median follow-up was 177 days (range, 12-1603). Median age was 64 years old (range, 29-98) and 47 (63%) were male. The main tumor types were melanoma (n = 47) and nonsmall-cell lung cancer (n = 19). Fifty-seven patients were treated with stereotactic radiosurgery (SRS) and 21 with whole-brain radiotherapy (WBRT). Most patients received single-agent ICB, though 4 patients received nivolumab and ipilimumab. Forty-one (53%) patients reported no neurologic toxicity. Grade 2 or greater neurologic toxicities were reported in 12 (21%) and 8 (38%) patients in the SRS and WBRT groups, respectively. WBRT was associated with a greater risk of any neurotoxicity, though there was no correlation between ICB agent and toxicity. Sequencing of ICB and RT (ie, <30 days vs <7) did not influence rates of toxicity. Conclusions: ICB during SRS or WBRT does not appear to worsen acute neurotoxicity compared to historical controls of RT alone.